CLinical EValuation of WEB 17 device in intracranial aneuRysms (CLEVER): procedural, 30-day and 1-year safety results for ruptured and unruptured aneurysms - Spelle Laurent; Costalat Vincent; Caroff Jildaz; Wodarg Fritz; Fischer Sebastian; Herbreteau Denis; Möhlenbruch Markus A.; Januel Anne-Christine; Papagiannaki Chrysanthi; Klisch Joachim; Numminen Jussi; Rautio Riitta; et al. (BMJ Publishing Group, 2025)
Background Intrasaccular flow disruption is an endovascular approach for the treatment of wide-neck aneurysms and, more specifically, wide-neck bifurcation aneurysms, which are challenging to treat with previously developed technologies. The Woven EndoBridge (WEB) device has demonstrated its efficacy and safety, for both unruptured and ruptured aneurysms.
Methods The CLEVER study was an observational, multicenter, prospective study conducted in 17 European investigational sites using the WEB 17 device, for the treatment of ruptured and unruptured aneurysms. The study objective was to provide safety and efficacy data on the WEB 17 device in the treatment of wide-neck bifurcation aneurysms. Imaging results were assessed independently by a Corelab and adverse events adjudicated by a Clinical Event Adjudicator. This analysis reports procedural results and safety at 30 days and 12 months.
Results A total of 163 patients (mean age 58.1 years; 68.1% women) with 103 unruptured aneurysms and 60 ruptured aneurysms were enrolled. Most aneurysms were located on the anterior communicating artery (ACom) (37.4%) or the middle cerebral artery (MCA) bifurcation (30.1%). Aneurysm widths ranged from 2.0–9.2 mm, and the mean sac width was 5.0 mm. The WEB procedure was successfully completed in 163 patients (100%). At the 12-month follow-up, major stroke events occurred in 3 of 163 patients (1.8%), and no device-related mortality was observed.
Conclusion Endovascular treatment of ruptured and unruptured wide-neck bifurcation aneurysms using WEB 17 is safe, with a low complication rate and no device-related mortality. In particular, none of the ruptured aneurysms bled again up to 1 year of follow-up.
Trial registration number NCT03844334.